Eksklusivisme dan Radikalisme dalam Kitab Ezra: Upaya Menelaah Penyebab Eksklusivisme dan Radikalisme Bangsa Israel dalam Kitab Ezra serta Menemukan Refleksi bagi Pembaca Kristen Indonesia pada Masa Kini - Awijaya, Agetta Putri (Indonesian Journal of Theology, 2019)
The story of Israel’s journey in the Book of Ezra provides a description of how exclusivism and radicalism were able to grow among the group of Israelites returning from exile with Ezra. By paying attention to the social and political dynamics underlying the writing of this book, the reader can suss out how the situation of historical events provoked concerns related to identity within Ezra’s own cohort, eventually changing them to become an exclusivist and radicalized group. This article presents an excavation of the social and political context for the Book of Ezra, including a critique concerning the point of view of its author. The purpose of such an excavation is to investigate how exclusivism and radicalism emerged in the post-exilic period. Through this critical reading, readers, especially Indonesian Christians, can see how the seeds of exclusivism and radicalism grew in this given group of people, as well as how to prevent these seeds from causing conflict in order to preserve the unity in diversity of Indonesia [cf. Bhinneka Tunggal Ika].